Utilization Of Financial Technology Services Media in Improving Customer Satisfaction PT. Shopee International Indonesia - Euis Komalawati; Rido Ariftio (Ilomata International Journal of Social Science, 2021)
Financial Technology is a new way of transacting that uses money and media that has elements of communication and technology in it. Along with the development of technology and lifestyle adaptation in society 5.0, Financial Technology becomes people's choice in shopping for needs and desires through a commercial online system (E-Commerce). Therefore, this study aims to find out and analyze financial technology service media utilization in improving customer satisfaction. Shopee International Indonesia. This research uses a qualitative approach and descriptive method with the selected research object of financial technology media Shopee International Indonesia. Data collection techniques used are interviews, observations and documentation. Based on the results of this study shows that service required a good relationship between customers and the company. The selection of online media or new media such as financial technology can be a communication link between consumer to consumer (C2C) and is supported by several service features that make it different between transactions through e-commerce media and conventional transactions, especially in creating customer satisfaction. The utilization of financial technology media involves customer relations, media services and impact on customer satisfaction